Expression of CBY and Methylation of CBY at Promoter Region in Human Laryngeal Squamous Cell Carcinoma. Issue 2 (March 2015) - Ren, Gang; Zhao, De-an; Xu, Jue; Li, Bo-an
Aims and Background: Chibby ( CBY ), a β-catenin binding partner, inhibits Wnt/β-catenin-mediated transcriptional activation by competing with Tcf/Lef factors for β-catenin binding and promoting the export of β-catenin from nucleus to cytoplasm. The regulatory effect of CBY in this signaling pathway suggests its biological importance as a potential tumor suppressor gene. The purposes of this study were to determine whether the expression of CBY was downregulated in human laryngeal squamous cell carcinoma (LSCC) samples, the CpG sites of CBY at the promoter region were methylated in these tumor samples, and reduced expression of CBY was induced by methylation of CBY promoters. Methods: CBY expression was investigated by quantitative real-time PCR and immunohistochemistry in samples from 36 LSCC patients. The methylation status of the CBY promoter was detected by methylation-specific PCR. Results: Compared with normal laryngeal mucosa, the expression of CBY was downregulated in LSCC samples. The reduced CBY expression rate was 58.33% (21/36) at the mRNA and 66.67% (24/36) at the protein level. The promoters of CBY were methylated in 12/36 tumor samples, partially methylated in 5, and unmethylated in 19 samples. The methylation rate including incomplete methylation was 47.22% (17/36) in tumor samples, while no methylation was detected in normal laryngeal squamous epithelium. Compared with the unmethylated group, the expression of CBY was significantly different in the methylated group (p<0.05) but similar in the partially methylated group (p>0.05). Conclusions: Our data indicate that CBY expression was downregulated in LSCC, which may be partially caused by methylation of CBY promoters.